2005
DOI: 10.1007/s11095-004-1873-z
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable, Extrusion-Free Method for Efficient Liposomal Encapsulation of Plasmid DNA

Abstract: This new method will enable the scale-up and manufacture of SPLP required for preclinical and clinical studies. Additionally, this method now allows for the acceleration of SPLP formulation development, enabling the rapid development and evaluation of novel carrier systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
249
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(259 citation statements)
references
References 45 publications
10
249
0
Order By: Relevance
“…C12-200-siRNA formulations were prepared using a method adapted from Jeffs et al (34) Briefly, C12-200, distearoyl phosphatidylcholine (DSPC), cholesterol and mPEG2000-DMG were solubilized in 90% ethanol at a molar ratio of 50∶10∶38.5∶1.5. The siRNA (or pool of siRNAs) was solubilized in 10 mM citrate, pH 3 buffer at a concentration of 0.4 mg∕mL.…”
Section: Methodsmentioning
confidence: 99%
“…C12-200-siRNA formulations were prepared using a method adapted from Jeffs et al (34) Briefly, C12-200, distearoyl phosphatidylcholine (DSPC), cholesterol and mPEG2000-DMG were solubilized in 90% ethanol at a molar ratio of 50∶10∶38.5∶1.5. The siRNA (or pool of siRNAs) was solubilized in 10 mM citrate, pH 3 buffer at a concentration of 0.4 mg∕mL.…”
Section: Methodsmentioning
confidence: 99%
“…The encapsulation efficiency of plasmid DNA contained in the prepared PEG-CLPs was determined by following a previously described protocol [26]. Briefly, we used PicoGreen (Molecular Probes, Eugene, OR, USA) a membrane impermeable dye that specifically binds to double-stranded DNA and is fluorescent.…”
Section: Measurement Of Pdna Encapsulation Efficiencymentioning
confidence: 99%
“…The resulting particle size was ,200 nm and was monodispersed. 19 LNPs have been evaluated in several pipelines of clinical trials as stable nucleic acid lipid particles (SNALP). 20, 21 Rodrigueza et al reported the preparation of lipid-based nanoparticle (PNT2258) loading of a 24-base DNA oligonucleotide using a one-step method that is similar to the method of SNALP preparation, 22 and such nanoparticles have been evaluated in clinical trials.…”
Section: Introductionmentioning
confidence: 99%